Study on liver arsenic level in antibiotic treated rats - Choudhry, Zubaida Khatoon; Afrin, Munira; Saleh, Ahmed Abu; Mojlish, UKF (Journal of Dhaka Medical College, 2013)
Rats treated with arsenic (1mg/L) in drinking ad libitum an increase in liver tissue arsenic was observed when orally pretreated with streptomycin (500mg twice daily). Inhibition of gut flora was confirmed by microscopic examination of stool. Control group showed a mean gut-bacterial count of 7.13-7.26×108cfu/g dry weight of stool, when administered with streptomycin orally (500mg twice daily) gut-bacterial count was not countable on day 7. Liver tissue arsenic level increased to 5.78 mg/g of liver tissue compared to that of the control group of 3.33mg/g of liver tissue. A decrease in gut-bacterial count of 2.83×108 cfu/g dry weight of stool was observed on day 14 in rats that were not pretreated with streptomycin but received only arsenic (1mg/L) in drinking water ad libitum throughout the study period. Increase in liver arsenic level in this group was almost similar to that of streptomycin pretreated rats. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15624 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 51-54